Implementasi Corporate Social Responsibility (CSR) Pt Pupuk Indonesia Berdasarkan ISO 26000 - Permatasari, Mayang; Saefullah, Saefullah; Budiman, Anwar (Peneliti.net, 2025)
Corporate social responsibility is social responsibility to society and the environment beyond economic responsibility, or a company's commitment to contributing to sustainable economic development. The problems discussed in this research are how to implement PT Pupuk Indonesia's corporate social responsibility based on ISO 26000? What obstacles does PT Pupuk Indonesia face in implementing Corporate Social Responsibility based on ISO 26000? Normative juridical research methods. In conclusion, PT Pupuk Indonesia uses international instruments in implementing its Corporate Social Responsibility program, namely ISO 26000 on Social Responsibility. In implementing CSR based on ISO 26000, PT Pupuk Indonesia implements CSR programs which are broadly aimed at four pillars, namely: Pillar Social (MSME Funding Program, Poverty Alleviation Program, Health Improvement Program, Community Education Program); Economic Pillar; Environmental Pillar; and the Law and Governance Pillar. In implementing PT Pupuk Indonesia's Corporate Social Responsibility there are several obstacles or factors that slightly hinder the implementation of CSR. These obstacles can be seen from several factors, including: Communication factors; Resource; Disposition; Bureaucratic Structure; Mapping Social Problems That Have Not Been Implemented Well; and Inappropriate Absorption of Corporate Social Responsibility Funds.